PENGARUH GAJI DAN DISPLIN KERJA TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN - MOHAMMAD BUKHORI (Jurnal Akademika, 2018)
The purpose of this study is to determine the effect of salary and disiplinkerja to work motivation, work motivation on employee performance, and the effect of salary and work discipline on employee performance through work motivation. Type of research used in this research is explanatory research and research method used is quantitative. The population in this study amounted to 47 employees of PT KAI (Persero) Stasiun Kertosono. The sample size is 35 employees by using purposive sampling technique. This study uses descriptive analysis and statistical analysis used to determine the elements - variable elements of salary, work discipline, work motivation and employee performance. Data processed using computer program SPSS for windowsver. 23 Based on the results of statistical analysis using path analysis, the salary variable has a direct influence on work motivation so that hypothesis 1 is accepted and the influence is significant. The discipline variable has a direct influence on work motivation, so hypotheses 2 is accepted and the effect is significant. And the salary variable has a direct influence on employee performance so that hypotheses 3 is accepted and the influence is significant. From the variable of work discipline has a direct influence on employee performance so that hypothesis 4 is accepted and significant. And the motivation variable has a direct influence on employee performance. This shows that the variable salary and work discipline give a significant influence on work motivation and employee performance either directly or indirectly. Keywords: salary, work discipline, work motivation, employee performance